The Paleoclimate Significance of the δ13C Composition of Individual Hydrocarbon Compounds in the Maoming Oil Shales, China - Cao, Xinxing; Song, Zhiguang; Wang, Sibo; Lyu, Puliang (Frontiers in Earth Science, 2021)
Maoming oil shales are typical low-altitude lacustrine sediments that were deposited during the late Paleogene. The hydrocarbon composition and compound specific stable carbon isotopic composition (δ13C) of organic matter in the profile samples of the oil shales have been analyzed. The results show that algae and aquatic plants are major parent sources of the organic matter in the oil shales associated with a small portion of terrestrial higher plant input. The δ13C composition of the bulk organic matter and the n-alkanes vary greatly on the profile from -26.9‰ to -15.8‰ and -31.7‰ to -16.2‰, respectively. While a good positive correlation among the δ13C composition of individual n-alkanes implies that these n-alkanes were originated from the similar source input. The δ13C composition of n-alkanes on the profile display a positive excursion trend from the bottom to the top and this excursion was likely related to the general decreasing trend of the partial pressure of atmospheric CO2 (pCO2) during the late Paleogene. The δ13C composition of the C30-4-methyl steranes range from -11.9‰ to -6.3‰, which is suggestive of Dinoflagellates related source input. Coincidently, the high abundance C33-botryococcanes were detected in the samples on the top section of the profile and display an extremely positive carbon isotopic composition of -4.5‰ to -8.4‰, suggesting that the lower partial pressure of atmospheric CO2 had triggered a bicarbonate consumption mechanism for Botryococcus braunii B.. Therefore, the δ13C composition of n-alkanes and C33-botryococcanes and their profile variation suggest that a general declining process associated with fluctuation in the partial pressure of atmospheric CO2 is likely the major reason for the rapid climate changes toward the end of the Late Paleogene.